From past to present: tracing the trends of diabetes drug trials in mainland China - Ma, Zengqing; Zhao, Xin; Lin, Yu; Zhang, Hong; Wu, Lianping; Tao, Yang; Shi, Hongjun; Li, Susu (Frontiers in Endocrinology, 2025)
BackgroundThis study aimed to analyze the changing trend of diabetes drugs clinical trials in China during 2013-2023, and provided a reference for the research and development of diabetes drugs.MethodsDiabetes drug clinical trial data were obtained from the registration and information disclosure platform of the National Medical Products Administration (NMPA) between January 1, 2013, and December 31, 2023. Trends of clinical trials on diabetes drugs were systematically analyzed in terms of characteristics, trial design, time trends, drug type, and indications.ResultsFrom 2013 to 2023, a total of 1,256 diabetes drugs clinical trials have been registered on the NMPA platform, of which 1056 were chemical drugs and 184 were biological products. The indications are mainly type 2 diabetes mellitus (n=1237, 98.49%). Among them, 838 clinical trials have been completed, 379 were proceeding, and 39 have been terminated or suspended. There were 42 international multi-center clinical trials, and the remaining 1034 clinical trials were domestic. Bioequivalence trials were 691, accounting for 55.02%, followed by 340 phase I clinical trials and 169 phase III clinical trials. The leading units were mostly distributed in eastern China. The proportion of clinical trial sponsorship from domestic pharmaceutical companies is higher than that from overseas companies.ConclusionsChina has made significant advancements in diabetes drug research and development over the past decade. However, problems such as serious drug homogeneity, and insufficient innovation have become increasingly prominent. The government, clinical trial institutions, and pharmaceutical companies must collaborate to promote the high-quality development of drug clinical trials.